Paraguay : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper analyzes the spillover effects of key external shocks on Paraguay. It presents an overview of Paraguay's major economic and financial linkages with the rest world, and quantifies the spillover effects of key external factors on the Paraguayan economy, using a vector autoregression approach. The empirical results suggest that global shocks have a significant impact on Paraguay's growth rate. The paper also highlights that output and exchange rate shocks stemming from Brazil and Argentina are also important, even after controlling for global factors.